Global Biases in Ecology and Conservation Research: Insight From Pollinator Studies - Skaldina, Oksana; Blande, James D. (Wiley, 2025)
In the fields of ecology and conservation, taxonomic and geographic biases may compromise scientific progress. Using pollinator research as a case study, we evaluate four drivers of these biases and propose solutions to address (i) untested generalisations from highly studied taxa, (ii) information accessibility, (iii) scattered environmental regulations and (iv) restricted infrastructure and funding resources. Expanding the taxonomic, functional and geographic breadth of research and legislation, and involving scientists in policymaking, can generate greater equity, accessibility and impact of future science. Using search engines in different languages, Open Access (OA) publishing and promoting mutually beneficial collaborations between scientists from developed and developing countries, may help to overcome geographic biases in research and funding. We suggest reviewing potentially similar biases and their drivers in other branches of ecology and conservation and identifying further ways to achieve information balance in science.